THE CORRELATION BETWEEN VOCABULARY MASTERY AND THE ABILITY IN WRITING RECOUNT TEXT FOR THE THIRD YEAR STUDENTS OF SMP NEGERI 34 PEKANBARU - Rahmatul Annisa Ramadhanti Badri; Eliwarti Eliwarti; Syofia Delfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to find out the correlation between vocabulary mastery and the ability in writing recount text by the third year students of SMP Negeri 34 Pekanbaru. The samples of the research were 35 students of IX class. The data were obtained from students’ vocabuary mastery and the ability in writing a recount text. The vocabuary test was used to know students’ vocabuary mastery and the writing test was used as the test to assess the students’ writing ability. The scores showed that students’ vocabulary mastery were good and the writing ability level were good as well. The mean score of vocabuary mastery was 71.20, while the mean score of writing ability was 70.71. The value of correlation coefficient was 0.750. Based on the interpretation by Sugiyono (2017) if the correlation value is between 0.600 – 0.799. It means that the study found that there was correlation between vocabulary mastery and the writing ability of the third year students of of SMP Negeri 34 Pekanbaru was high. It’s suggested that vocabulary is important skills necessary for students to learn English because it is the basis for the expansion of all the other skills especially writing skills.Key Words: Vocabulary, Mastery, Ability, Writing, Recount Text